Institutionalized Ageism: A Theoretical Review - Teixeira, Selena Mesquita de Oliveira (2018)
Considering the problems associated with the social demands and patterns that affect old age, a theoretical review of aspects that collaborate to institutionalize the prejudice directed at the elderly, as well as the stereotypes that support this phenomenon, are investigated. The ageism is manifested in a veiled way, leading people to confer positive content to their individual perception in relation to old age and to explain ageism as a collective phenomenon.